2021
DOI: 10.3390/ani11051464
|View full text |Cite
|
Sign up to set email alerts
|

The Binding of Free and Sulfated Androstenone in the Plasma of the Boar

Abstract: Androstenone circulates in the plasma bound to albumin before accumulating in the fat, resulting in the development of boar taint. Androstenone sulfate is more abundant in the circulation than free androstenone; however, it is unclear how androstenone sulfate is transported in the plasma and if steroid transport affects the development of boar taint. Therefore, the purpose of this study was to characterize the binding of androstenone sulfate in boar plasma and determine if variability in steroid binding affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Human embryonic kidney (HEK293FT) cells purchased from ATCC (Manassas, VA. USA) were used to synthesize [ 3 H]-androstenone sulfate as previously described by Bone and Squires [ 11 ]. Briefly, confluent HEK293FT cells were transfected with 6 µg/plate of the porcine sulfotransferase SULT2A1 (pSULT2A1) expression vector constructed as previously described by Laderoute et al [ 2 ], and, after 48 h, treated with radiolabeled [ 3 H]-androstenone (8 million CPM, 36 µCi/µmol, 0.1% ethanol).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Human embryonic kidney (HEK293FT) cells purchased from ATCC (Manassas, VA. USA) were used to synthesize [ 3 H]-androstenone sulfate as previously described by Bone and Squires [ 11 ]. Briefly, confluent HEK293FT cells were transfected with 6 µg/plate of the porcine sulfotransferase SULT2A1 (pSULT2A1) expression vector constructed as previously described by Laderoute et al [ 2 ], and, after 48 h, treated with radiolabeled [ 3 H]-androstenone (8 million CPM, 36 µCi/µmol, 0.1% ethanol).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, a metabolite tentatively identified as androst-3-enol-3-sulfate was detected by liquid chromatography–mass spectrometry from Leydig cell culture and was found to return free androstenone, and not a hydroxylated metabolite, following chemical removal of the sulfate group [ 9 ]. Additionally, we have previously demonstrated that androstenone sulfate has a low binding capacity for porcine albumin, which is the carrier protein responsible for the transport of various steroids in the boar including free androstenone [ 10 , 11 ]. Consequently, androstenone sulfate circulates predominantly unbound in the porcine plasma and is presumably readily available for uptake into peripheral tissues [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation